The management of infertility associated with polycystic ovary syndrome - Homburg, Roy (BioMed Central, 2003)
Polycystic ovary syndrome [PCOS] is the commonest cause of anovulatory infertility. Treatment modes available are numerous mainly relying on ovarian stimulation with FSH, a reduction in insulin concentrations and a decrease in LH levels as the basis of the therapeutic principles. Clomiphene citrate is still the first line treatment and if unsuccessful is usually followed by direct FSH stimulation. This should be given in a low dose protocol, essential to avoid the otherwise prevalent complications of ovarian hyperstimulation syndrome and multiple pregnancies. The addition of a GnRH agonists, while very useful during IVF/ET, adds little to ovulation induction success whereas the position of GnRH antagonists is not yet clear. Hyperinsulinemia is the commonest contributor to the state of anovulation and its reduction, by weight loss or insulin sensitizing agents such as metformin, will alone often restore ovulation or will improve results when used in combination with other agents. Laparoscopic ovarian drilling is proving equally as successful as FSH for the induction of ovulation, particularly in thin patients with high LH concentrations. Aromatase inhibitors are presently being examined and may replace clomiphene in the future. When all else has failed, IVF/ET produces excellent results. In conclusion, there are very few women suffering from anovulatory infertility associated with PCOS who cannot be successfully treated today.